Foreign investor flows and blue chip stock returns - Adaoglu, Cahit; Katircioglu, Salih Turan (Emerald Group Publishing Ltd, 2013)
Purpose - The purpose of this paper is to investigate the direction of causality between the monthly stock returns and the monthly net foreign investor flows, and the existence of feedback trading by foreign investors for the blue chip stocks of the Istanbul Stock Exchange (ISE), an emerging stock market. Design/methodology/approach - Monthly net foreign investor flows and stock returns of blue chip stocks for the period January 1997-June 2010 are used. Particularly, taking into account the structural changes in the foreign investor trading activity, the study focuses on the two sub-periods before and after the start of European Union (EU) accession negotiations of Turkey. The study uses the bivariate VAR Granger causality approach, impulse response analysis and uses regressions with the vector autoregressive structure and contemporaneous structure (without lag). Findings - Unidirectional Granger causality running from monthly stock returns to monthly net foreign investor flows is detected for the pre-EU accession negotiations period accompanied by a negative feedback trading effect, but a causality relationship and feedback trading could not be established for the post-EU accession negotiations period. The relationship is a contemporaneous one rather than a lagged relationship for the latter period. Research limitations/implications - The studies on the impact of foreign investor flows utilize daily and/or monthly data depending on availability. For the ISE, only monthly full data is available. Further research on the effects of foreign investors in the ISE such as the base broadening and price pressure effects should be undertaken. Practical implications - The findings are particularly useful for financial managers, portfolio managers, traders, domestic and foreign investors dealing with the ISE. Originality/value - The article contributes to the limited empirical evidence on the price effects of foreign investor flows in the stock exchanges located in Eastern Europe, Middle East and surrounding countries. The study also considers the significant increase in the amount of foreign investor flows after the start of EU accession negotiations of Turkey and detects a change in the price effect. Unlike the strong empirical evidence of positive feedback trading in the finance literature, negative feedback trading is detected in the ISE, but only for the period before the start of EU accession negotiations. Using monthly data, any feedback trading could not be detected for the period after.
Keywords: Turkey; Returns; Stock prices; International investments; Foreign investors; Price effect; Stock return; Causality; Feedback trading; Impulse response; Istanbul Stock Exchange